Analisis Sentimen Komentar Audiens terhadap Tayangan 'LIVE - Anies dan Efek Kejut di Pilkada Jakarta | ROSI' pada Kanal YouTube KOMPASTV: Studi tentang Persepsi Publik di Media Digital. - Anggraini, Dina Juniar; Septian Dwi Putri; Maria (CARAKA : Indonesia Journal of Communication, 2024)
This study analyses audience sentiment toward the program "LIVE - Anies and Efek Kejut di Pilkada Jakarta | ROSI" on KompasTV's YouTube channel to understand public perception in digital discourse. Using a descriptive-exploratory approach, data consisting of 1,742 comments were collected via web scraping with Python and processed through preprocessing, translation, and sentiment classification using TextBlob. The analysis revealed that 53.1% of the comments were positive, 36.61% neutral, and 10.29% negative. A word cloud visualization highlighted the dominance of terms related to Anies Baswedan as the discussion's focal point. Furthermore, contextual and semantic analysis of several comments emphasized the limitations of automated classification in accurately capturing sentiment. The study underscores the necessity of integrating quantitative and qualitative methods to gain comprehensive insights into public opinion on digital platforms. These findings demonstrate the critical role of digital media, particularly YouTube, as an interactive arena for political communication. Keywords: Sentiment Analysis, Political Communication, Public Perception, YouTube, Pilkada 2024.